Working Capital Position of Company: Managing Working Capital for Business Profitability (Journal of Advances and Scholarly Researches in Allied Education, 2012)
A successful salesprogramme is necessary for earning profits by any business enterprise. However,sales do not convert in to cash instantly; there is invariably a time lacbetween the sale of goods and the receipt of cash. There is therefore, need forworking capital in the form of current assets to deals with the problem arisingout of the lack of immediate realization of cash against goods sold. Therefore,sufficient working capital is necessary to sustain sales activity. Working capital represents the short-term strength of thefirm. It is the excess of current assets over the current liabilities. The termcurrent assets refers to assets which in the normal course of business getconverted into cash without diminution in value over a short period, usuallynot exceeding one year or length of operating cycle whichever is more. Currentliabilities are those liabilities which at the inception are required to bepaid is short period, normally a year.